Alveolar soft part sarcoma with multiple brain and lung metastases in pregnancy: A case report and literature review. Issue 46 (November 2017) - Wang, Yubo; Cui, Jiayue; Yan, Xu; Jin, Rihua; Hong, Xinyu
Abstract: Rational: Alveolar soft part sarcomas (ASPSs) with multiple brain metastases in pregnancy is a rare entity. Patient concerns: We report our experience with a 19-year-old pregnant woman who presented with intermittent headaches and vomiting at 38 weeks gestation. Diagnoses: The patient was initially diagnosed as brain metastasis according to computed tomography and magnetic resonance imaging (MRI) imaging. Interventions: Cesarean section and craniotomy (complete resection of both brain metastatic lesions) was performed sequentially. Outcomes: A healthy baby girl was delivered safely and no neonatal malformations were found. Histological analysis confirmed the diagnosis of ASPS. Follow-up MRI performed 10 months after surgery revealed no residual tumor or signs of recurrence. Lessons: We report a case of ASPS with multiple brain and lung metastases in a pregnant woman. We recommend timely MRI examination for diagnosis and have discussed the approach to the treatment of pregnant women with brain metastasis.